Analysis of Exchange Rate Stability on the Economic Growth Process of a Developing Country: The Case of South Africa from 2000 to 2023 - Collin Chikwira; Mohammed Iqbal Jahed (Economies)
This study examines the impact of exchange rate stability on the economic growth of South Africa from 2000 to 2023, a period characterised by significant political and economic changes. Exchange rate stability is critical for developing countries, affecting key macroeconomic variables such as trade balances, foreign direct investment (FDI), and inflation. For emerging economies like South Africa, maintaining a stable exchange rate can reduce uncertainty in international transactions, foster investor confidence, and support sustainable economic development. This research explores whether consistent exchange rate management has positively influenced South Africa’s economic trajectory, particularly by mitigating the adverse effects of global shocks and domestic volatility. Using the EasyData online database, which contains yearly time series data, the method of analysis adopted by the research is the ordinary least squares (OLS) regression method. The findings show that while exchange rate stability positively impacts GDP, the influence of FDI and political risk is more substantial. These results underscore the importance of fostering a stable economic environment through sound exchange rate policies, political stability, and efforts to attract foreign investments to ensure long-term economic growth.